Government Communication and Social Cohesion: A Contradiction of Words in Action? - Vasanthakokilam Naidoo (Cosmopolitan Civil Societies: An Interdisciplinary Journal)
This article presents the findings of a 2022 doctoral study that examines the government's communication for social cohesion in the eThekwini Metropolitan Municipal Area, also known as the city of Durban, in South Africa. The findings and recommendations are applicable to social cohesion globally as evidenced by news reports of violence against women in New York, anti-LGBTQIA+ laws in Uganda, anti-Moslem and anti-Christian sentiments. The study employing a Likert-type questionnaire and focus group discussions revealed that government communication, measured against the Social Cohesion Index, surreptitiously changes mindsets but is undermined by its actions. Participants perceive slow service delivery, corruption, unfair implementation of affirmative action, racism, homo- and trans-phobia, marginalization of the disability sector, tribalism and dearth of leaders, as hindrances. The LGBTQIA+ and disability sectors are victimised limiting their inclusion in the economy and access to services. Recommendations include appointing credible leaders as social cohesion ambassadors, fair implementation of affirmative action policies and communication substantiated by tangible public services.